Practical synthesis of N-(di-n-butylamino)methylene-protected 2-aminopurine riboside phosphoramidite for RNA solid-phase synthesis - Neuner, Eva (Monatsh Chem, 2019)
[Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00706-019-02502-7) contains supplementary material, which is available to authorized users.